Combating Anti-Feminism and Building Strategies for Gender Equality - Mariana Fagundes-Ausani (Politikon)
This study examines digital feminist media outlets in Brazil and France, exploring their strategies to promote gender equality and combat hate speech. Focusing on three outlets from each country, the research employs a multi-site ethnographic approach, including 63 in-depth interviews with content producers, support teams, and audiences. The findings reveal that discovering sexist and exclusionary sociopolitical structures often catalyzes engagement in feminist activism, with emotional responses—particularly anger and frustration—serving as primary drivers for action. Engagement in digital feminist spaces fosters collective exchange and creates connections extending beyond the digital sphere. The research highlights the complex interplay between digital platforms, feminist ideology, and grassroots activism in shaping contemporary gender equality movements, contributing to our understanding of how digital feminist media navigate online activism challenges while fostering community and driving social change.